Research in the Social Scientific Study of Religion, Volume 18 2007
DOI: 10.1163/ej.9789004158511.i-301.91
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction and spirituality in adolescents

Abstract: The association between life satisfaction and dimensions of religio sity/spirituality was explored in an ethnically and denominationally diverse sample of 615 adolescents using the Satisfaction with Life Scale and the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS). Results indicate that most dimensions of religiosity and spirituality are associated with life satisfaction, but that Daily Spiritual Experiences accounts for the largest amount of variance in the models, and attenuates the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 0 publications
3
20
0
1
Order By: Relevance
“…These findings appear to be in agreement with those of other studies dealing both adults and adolescents, and with different religious beliefs (Abdel-Khalek, 2006;AbdelKhalek & Lester, 2007;Abdel-Khalek & Naceur, 2007;Abdel-Khalek & Thorson, 2006;Argyle, 2001;Barkan & Greenwood, 2003;Ellison, 1991;Francis et al, 2000;Francis et al, 2003;French & Joseph, 1999;Kelley & Miller, 2007;Wills, 2009). Moreover, some studies have also failed to determine a significant relation between religion and negative affection (Clark & Watson, 1999;Watson & Clark, 1993).…”
Section: 26supporting
confidence: 89%
See 1 more Smart Citation
“…These findings appear to be in agreement with those of other studies dealing both adults and adolescents, and with different religious beliefs (Abdel-Khalek, 2006;AbdelKhalek & Lester, 2007;Abdel-Khalek & Naceur, 2007;Abdel-Khalek & Thorson, 2006;Argyle, 2001;Barkan & Greenwood, 2003;Ellison, 1991;Francis et al, 2000;Francis et al, 2003;French & Joseph, 1999;Kelley & Miller, 2007;Wills, 2009). Moreover, some studies have also failed to determine a significant relation between religion and negative affection (Clark & Watson, 1999;Watson & Clark, 1993).…”
Section: 26supporting
confidence: 89%
“…Several studies in the literature examine the direct relation of religiousness and spirituality with subjective well-being of adults, many of them reporting either modest or low levels of positive relation regarding the relevant variables and subjective well-being of adults (Argyle, 2001;Clark & Watson, 1999;Ellison, 1991;Francis, Jones, & Wilcox, 2000;Francis, Robbins, & White, 2003;French & Joseph, 1999;Kelley & Miller, 2007;Watson & Clark 1993;Wills, 2009). Studies conducted on university students have revealed a positive relation between subjective well-being and religion, while they have reported a negative relation between religion and psychopathology (Abdel-Khalek, 2006;Abdel-Khalek & Lester, 2007;Abdel-Khalek & Naceur, 2007;Abdel-Khalek & Thorson, 2006).…”
Section: Relations Between Subjective Well-being and Religionmentioning
confidence: 99%
“…In this regard, studies have indicated a relationship between spirituality and various outcomes, including psychological well-being as well as mental and physical health (31)(32)(33). In fact, spirituality can positively affect the sense of satisfaction in life (34).…”
Section: Discussionmentioning
confidence: 99%
“…Zullig, Ward, and Horn (2005) found that college students who are spiritual or religious are likely to view themselves as healthier, and this view is likely to be linked to greater life satisfaction as well. Kelley and Miller (2007) also found that aspects of spirituality and religiosity were linked to life satisfaction, but that "Daily Spiritual Experiences" (daily interactions with the transcendent) contribute the most. Gauthier, Christopher, Walter, Mourad, and Marek (2006) found a positive correlation between religiosity and life satisfaction, but this effect was only found in women.…”
Section: Spirituality And/or Religiositymentioning
confidence: 95%